Global value chains in the Pacific island countries: Patterns and structure - Upalat Korwatanasakul (Asian Development Bank Institute (ADBI), 2023)
This study investigates the patterns of global value chain (GVC) participation of Pacific island countries (PICs) at the country, industry, and firm levels, utilizing UNCTAD-Eora GVC data (1999-2018) and the World Bank's Enterprise Survey data (2009 and 2015). It also uses the survey data to examine the relationship between firm and country characteristics and firm-level GVC participation. At the country level, the study found a limited role of the PICs in global and regional production networks, hindering foreign technological and knowledge transfer, industrialization, and economic development, while, at the industry level, the PICs generally engage in low-value-added activities. The firm-level analysis reveals that the PICs' domestic firms, particularly SMEs, face difficulties joining value chains. Although firm characteristics, i.e., labor productivity and quality certification, are essential for firms to engage in GVCs initially, they are insufficient to deepen the GVC participation level. The analysis also emphasizes the significance of macro-level business-enabling environment factors, including good governance, trade openness, and foreign direct investment.
Keywords: F13; F14; O24; 330; global value chain; islandness; Pacific island; production network; trade in value added